INDONESIAN TRADE PERFORMANCE WITHIN ASEAN FREE TRADE AREA (AFTA): INTRA-INDUSTRY TRADE ANALYSIS - Heru Wibowo (Widyariset, 2013)
SEAN has moved forward by establishing the ASEAN Free Trade Area (AFTA) in 28 January 1992. The main objective of AFTA is to promote ASEAN countries competitive advantages by eliminating tariff and non-tariff barrier under AFTA’s Common Effective Preferential Tariff (CEPT) scheme. Indonesia participation in AFTA is worth noting since CEPT covers significant amount of Indonesian exports and imports. This paper investigates Indonesia trade performances under AFTA employing intra-industry trade analysis. It uses three digit SITC derived from UN COMTRADE. The results show that during 1992–2010, Indonesia and ASEAN trade was highlighted by intra rather than inter-industry trade, particularly for manufacture commodity. Further inter-temporal analysis confirms this finding with increasing trend of intra-industry trade for non-manufactured commodity. Nonetheless, Indonesian sectoral performance was less competitive compare to other ASEAN countries. This study suggests that Indonesia may enhance the advantage of being AFTA’s member by, for example, creating a conducive investment environment.